Development of Interactive Learning Media Assisted by Articulate Storyline 3 to Train High School Students' Problem-Solving Skills - Wahyuni, Messy; Medriati, Rosane; Setiawan, Iwan (Universitas Syiah Kuala, 2024)
As a result of the PISA test, the science category indicates that students' problem-solving abilities in Indonesia fall within the low category. This study aims to describe (1) the feasibility of interactive learning media assisted by the Articulate Storyline 3 application, (2) the improvement of students' problem-solving abilities after using learning media assisted by Articulate Storyline 3, and (3) student responses to Articulate Storyline 3-assisted learning media. This research uses the Research and Development (RD) method with the ADDIE model. The research subjects are students of the 10th grade at Public High School 8 in Bengkulu City. The research instruments used are interview sheets, observations, needs analysis, expert validation, pretest-posttest, and student response questionnaires. Data collection is done through observations, interviews, and questionnaires. Data were analyzed using quantitative analysis techniques and summarized qualitatively. The product generated is interactive learning media assisted by Articulate Storyline 3, with expert validation results showing a 90% percentage in the highly feasible category. Students' problem-solving abilities, tested with the N-gain test, obtained a score of 0.65, indicating moderate improvement, and student responses received an 83% percentage in the very good category. Based on these results, it can be concluded that the development of interactive learning media assisted by Articulate Storyline 3 to train students' problem-solving abilities is highly feasible